2003
DOI: 10.1021/la035063k
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Behavior of Short-Chain PDMS-b-PEO Diblock Copolymers in Aqueous Solutions

Abstract: Short-chain poly(dimethylsiloxane)−poly(ethylene oxide) (PDMS-b-PEO) diblock copolymers with different ratios of the hydrophilic to hydrophobic segments were synthesized via coupling of end-functionalized PDMS and PEO homopolymers. Their aggregation behavior was investigated by tensiometry, fluorescence, and cryogenic transmission electron microscopy. Interestingly, the critical aggregation concentration of the surfactants increased with increasing length of the hydrophobic chain. The electron microscopy studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 14 publications
4
51
1
Order By: Relevance
“…The self-arrangement of PDMS-g-POEM comb copolymer into uniform spherical micelles in a polar solvent such as ethanol was proved by the EF-TEM image shown in [26][27][28][29] Micelle morphology is largely dependent on experimental parameters such as the molecular weight of the polymers, relative chain length ratio of each block, type of medium, and concentration. The shape and size of PDMS-g-POEM comb copolymer with a molecular weight of 14,000 gmol -1 in ethanol (1 wt%) are comparable to those reported by Wang et al 29 ; these authors reported that a POEGMA 11.6 -PDMS 11 - 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 POEGMA 11.6 triblock copolymer with a molecular weight of 9400 gmol -1 could self-assemble into spherical single micelles with a diameter of approximately 100 nm in aqueous solution (0.5 mg mL -1 ).…”
Section: Characterization Of Pdms-g-poem Comb Copolymermentioning
confidence: 99%
“…The self-arrangement of PDMS-g-POEM comb copolymer into uniform spherical micelles in a polar solvent such as ethanol was proved by the EF-TEM image shown in [26][27][28][29] Micelle morphology is largely dependent on experimental parameters such as the molecular weight of the polymers, relative chain length ratio of each block, type of medium, and concentration. The shape and size of PDMS-g-POEM comb copolymer with a molecular weight of 14,000 gmol -1 in ethanol (1 wt%) are comparable to those reported by Wang et al 29 ; these authors reported that a POEGMA 11.6 -PDMS 11 - 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 14 POEGMA 11.6 triblock copolymer with a molecular weight of 9400 gmol -1 could self-assemble into spherical single micelles with a diameter of approximately 100 nm in aqueous solution (0.5 mg mL -1 ).…”
Section: Characterization Of Pdms-g-poem Comb Copolymermentioning
confidence: 99%
“…[26] This feature can be used to determine the CMC of a copolymer solution. Figure 4 presents the relationship between the surface tension of copolymer solutions and concentration.…”
Section: Thermoresponsive Behavior Of Copolymer Solutionmentioning
confidence: 99%
“…[15][16][17] Previous studies have also reported the utilization of amphiphilic BCPs to prepare crosslinked hydrogels for tissue engineering applications. 18,19 Several approaches have been reported to combine PEG and PDMS; mainly through covalently linking linear PEG with linear PDMS to form a diblock copolymer, [20][21][22] end-capping linear PEG with linear PDMS to form a triblock copolymer, 23,24 and end-capping linear PDMS with linear PEG to form a triblock copolymer. 10,25,26 Other examples include a random-grafted PEG/PDMS copolymer 27 and a commercially available grafted PEG along a PDMS backbone.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Past studies have mainly focused on the selfassembly of linear-linear PEG/PDMS diblock copolymers where the formation of micelles and vesicles was reported. 20,22,30,31 These self-assembled structures have the potential to be utilized as nanocarriers in drug delivery system. 31 The stability of nanoparticles is a crucial condition for applications such as controlled drug delivery and release.…”
Section: Introductionmentioning
confidence: 99%